Sport science and coaching in paralympic cycling - Burkett, B. J.; Mellifont, R. B. (International Journal of Sports Science and Coaching, 2008)
This research documents the sport science initiatives of the Australian Cycling team in preparation for the 2004 Athens Paralympic Games. The research was driven by the head coach of the cycling program with biomechanical and physiological measures made during competition and/or in a controlled laboratory for six Paralympic cyclists. Half the group modified their setup with seat height decreases within a range of 10-19 mm, the other half with seat height increases within a range or 3-12 mm. All riders required seat fore/aft positioning adjustments of up to 30 mm forward to centre the knee joint over the pedal spindle. The pelvic angle rotation changed by an average of 7 degrees positive tilt (range 5-14 degrees). Relatively simple adjustments to one individual's setup reduced the cyclist's frontal-surface height by 0.22 m, with no significant change in power output. The integration of sport science with a high-performance coaching program can enhance the athlete's performance and safety. The outcomes of this specific research on elite athletes with a disability have guided the future coaching of the national team.